2017
DOI: 10.1007/s40520-017-0829-1
|View full text |Cite
|
Sign up to set email alerts
|

The rate of velocity development associates with muscle echo intensity, but not muscle cross-sectional area in older men

Abstract: The examination of mechanisms contributing to the age-related reductions in rapid velocity development is limited. The purpose of this study was to examine the influence of muscle cross-sectional area (CSA) and echo intensity (EI) on plantarflexor rate of velocity development (RVD) in older adults. Twenty-two men (mean ± SD age = 69 ± 3 years) performed three maximal plantarflexion voluntary isokinetic muscle actions at a velocity of 2.09 rad · s. Peak RVD was determined as the peak derivative of the velocity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…This finding seems to agree with a variety of studies conducted in older adults who, despite showing worse muscle quality than younger cohorts, typically show EI mean values ≤ 150 A.U. [ 26 28 ]. It should be noted, however, that the results of the present study are exclusive to the vastus lateralis, young females, the conditions provided by the study design, and the B-mode ultrasonography device and settings utilized by our laboratory.…”
Section: Discussionsupporting
confidence: 91%
“…This finding seems to agree with a variety of studies conducted in older adults who, despite showing worse muscle quality than younger cohorts, typically show EI mean values ≤ 150 A.U. [ 26 28 ]. It should be noted, however, that the results of the present study are exclusive to the vastus lateralis, young females, the conditions provided by the study design, and the B-mode ultrasonography device and settings utilized by our laboratory.…”
Section: Discussionsupporting
confidence: 91%
“…Measures of skeletal muscle structure obtained using diagnostic ultrasonography have been found to be related to measures of force and physical function (30,33,46,48,(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…EI is thought to be a non-invasive surrogate measure of muscle quality, as increased EI is associated with infiltration of intramuscular fat, collagen, and fibrous and connective tissue (10,(12)(13)(14). Although numerous investigations have demonstrated that muscle EI is related to functional ability, strength, and power (3,6,(13)(14)(15)(16)(17)(18)(19), studies using EI as a proxy of muscle quality after resistance training have generated inconsistent results (4,6,13,(20)(21)(22)(23), leading researchers to question the true physiological interpretation of muscle EI (24).…”
Section: Introductionmentioning
confidence: 99%